Cognitive effects of unilateral thalamotomy for tremor: a meta-analysis. Issue 6 (4th November 2022) - Rohringer, Camryn R; Sewell, Isabella J; Gandhi, Shikha; Isen, Jonah; Davidson, Benjamin; McSweeney, Melissa; Swardfager, Walter; Scantlebury, Nadia; Swartz, Richard H; Hamani, Clement; Giacobbe, Peter; Nestor, Sean M; et al.
Abstract: Tremor is a debilitating symptom that can lead to functional impairment. Pharmacotherapy is often successful, but up to 50% of patients are resistant to medications or cannot tolerate side effects. Thalamotomy to the ventral intermediate nucleus of the thalamus is a surgical intervention for refractory tremor. Thalamotomy surgeries include radiofrequency and incisionless procedures, such as Gamma Knife radiosurgery and magnetic resonance-guided focused ultrasound. Cognitive changes following thalamotomy have been inconsistently reported across studies. We performed a meta-analysis to summarize the impact of unilateral thalamotomy to the ventral intermediate nucleus of the thalamus across multiple cognitive domains. We searched MEDLINE, Embase Classic, Embase, and EBM Reviews for relevant studies. Neuropsychological tests were categorized into seven cognitive domains: global cognition, verbal memory, non-verbal memory, executive function, phonemic fluency, semantic fluency, and visuospatial processing. We calculated standardized mean differences as Hedges' g and 95% confidence intervals of the change between pre- and postoperative cognitive scores. Pooling of standardized mean differences across studies was performed using random-effects models. Risk of bias across studies and quality of evidence for each cognitive domain were assessed with the National Institute of Health quality assessment tool and the GRADEpro Guideline Development Tool, respectively. Of the 1, 251 records reviewed, eight studies met inclusion criteria. We included 193 patients with essential tremor, Parkinson's disease, or multiple sclerosis in the meta-analysis. There was a small significant decline in phonemic fluency (standardized mean difference = -0.29, 95% confidence interval: [-0.52, -0.05], p = 0.017) and a trend towards a decline in semantic fluency (standardized mean difference = -0.19, 95% confidence interval: [-0.40, 0.01], p = 0.056). No postoperative changes were observed in the other cognitive domains (p values >0.14). In secondary analyses, we restricted the analyses to studies using magnetic resonance-guided focused ultrasound given its growing popularity and more precise targeting. In those analyses, there was no evidence of cognitive decline across any domain (p values >0.37). In terms of risk of bias, five studies were rated as "good" and three studies were rated as "fair". According to GRADEpro guidelines, the certainty of the effect for all cognitive domains was low. This study provides evidence that unilateral thalamotomy to the ventral intermediate nucleus of the thalamus is relatively safe from a cognitive standpoint, however, there may be a small decline in verbal fluency. Magnetic resonance-guided focused ultrasound might have a more favourable postoperative cognitive profile compared to other thalamotomy techniques. Abstract : Based on a meta-analysis of eight studies, Rohringer, Sewell et al. report that unilateral ventral intermediate nucleus thalamotomy for tremor is relatively safe from a cognitive standpoint. The only cognitive domain to show a small postoperative decline was verbal fluency, all other domains remained stable. Graphical Abstract: Graphical Abstract